2018
DOI: 10.1002/dc.23901
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the benefit and use of the new terminology in endometrial cytology reporting system

Abstract: These data suggest that patients with ATEC-US results can be followed up for at least three months, and the introduction of the NTEMC system decreased the number of unnecessary endometrial biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In this report, we have shared the advantages of the LBC method applied to the cytologic diagnosis of endometrial lesions. The success of "TYS reporting format" will depend on the pathology and gynecologic oncology communities working collectively to improve this diagnostic standardization and to optimize its impact on patient care [78].…”
Section: Resultsmentioning
confidence: 99%
“…In this report, we have shared the advantages of the LBC method applied to the cytologic diagnosis of endometrial lesions. The success of "TYS reporting format" will depend on the pathology and gynecologic oncology communities working collectively to improve this diagnostic standardization and to optimize its impact on patient care [78].…”
Section: Resultsmentioning
confidence: 99%
“…The new terminology for endometrial cytology has been introduced and now TYSEC system is usefully utilized. [1][2][3][4][5] However, diagnosis of gray zone category, ATEC, especially ATEC-US implies that clinicians would perform unnecessary biopsies. Accurate cytological diagnosis is required to maximize the merit of cytology, which seems less harmful than biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that nearly 10% of the cases assigned to cytological ATEC-US category had corresponding malignant histology. [3][4][5] Although cytological gray zone category intrinsically has some amount of corresponding malignant histology, if it is large, it could cause a problem for managing patients with a cytological diagnosis of ATEC-US. Therefore, it would be ideal to minimize the number of cytological diagnosis of ATEC.…”
mentioning
confidence: 99%
“…21 However, several studies showed that increasing number of cases in gray zone category, especially ATEC-US in TYSEC, could cause problem in managing patients. [22][23][24] To solve the problem, a new approach to improve diagnostic accuracy have been expected. accuracy of endometrial carcinoma using thin-layer samples.…”
Section: Diagnostic Classification Of Endometrial Cytologymentioning
confidence: 99%